Strengthening behaviour of tin slag polymer concrete column with various confinement materials for structural application - Muhamad Soffi, Manda (2024)
Tin slag (TS) particle wastes are abundant potential resources originated from tin smelting process and has been introduced as aggregates in tin slag polymer concrete (TSPC). TSPC is a newly particulate reinforced composite material and previous studies have presented the potential of TSPC column strengthening using GFRP and CFRP reinforcement through external means. However, the strengthening behaviour of TSPC through other type of materials is still unknown. Therefore, in this research, the potential of TSPC column strengthening has been further explored with the application of other FRP composites and metallic materials. The TSPC column core samples have been prepared with uniform aggregates of fine TS particles (< 1 mm) and polyester resin with 1 % MEKP. The wet mixture of aggregates and resin (70:30) was poured into 50 mm PVC pipe as mold and cured for 3 days at room temperature. After demolding, the TSPC core columns underwent splitting tensile and compression tests to obtain control data for compressive strength prior to jacketing. The remaining samples were confined with GFRP, CFRP, BFRP, AFRP, Hybrid FRP, and mild steel tubes to strengthen the column before undergoing compression testing. In addition to that, empirical analysis has been performed by employing previous mathematical model to evaluate confined TSPC performance. Then, FEM model has also been developed using ABAQUS to evaluate TSPC confined GFRP and CFRP for numerical analysis followed by parametric study to simulate maximum number of FRP confinement layers on TSPC column for optimum compressive strength enhancement. The compressive strength of the unconfined TSPC column (TSPC-UC) was 59.19 MPa. With the application of lateral confinement, the compressive strength has been enhanced by a different percentage depending on the type of confinement material employed. The highest compressive strength enhancement was TSPC confined mild steel (TSPC-FM) with 131.84 MPa which indicates 122.74% of strength increment compared to TSPC-UC. The following strength enhancements on other variations of test samples from highest to lowest were TSPC confined AFRP (TSPC-AF), TSPC confined CFRP (TSPC-CF), TSPC confined GFRP (TSPC-GF) and TSPC confined BFRP (TSPC-BF) with 114.24 MPa, 108.77 MPa, 85.54 MPa and 81.52 MPa. The equivalent percentages of strength enhancement from TSPC-UC for TSPC-AF, TSPC-CF, TSPC-GF and TSPC-BF were 93.00%, 83.76%, 44.52% and 37.73%, respectively. Both numerical and empirical studies on TSPC confined and unconfined, exhibit good agreement with experimental results. Finally, optimisations that have been performed using the FEM model through a parametric study by varying the number of confinement layers for GFRP and CFRP materials have revealed that three layers of FRP confinement on TSPC columns were likely to be the number of saturation layers of FRP confinement materials for maximum compressive strength enhancement. To conclude, this research has provided studies through experimental work, empirical and numerical analysis as well as optimisation processes on TSPC confinement. All studies have provided good findings based on research objectives. In general, as a new particulate reinforced composite material, this research has contributed in providing large fundamental data on TSPC, which will benefit the research community, especially those of similar interest. Future research on TSPC may address extensive FEM study, analytical study, flexural property and internal reinforcement studies to further investigate its potential before an actual application could be implemented commercially.